The Mediator Role of Procedures in the Relationship between Business Setup Time and Starting New Business - M. Çağrı Pehlivanoğlu; Mustafa Emre Civelek; Selim Aykaç (Journal of International Trade, Logistics and Law, 2024)
Starting a new business can sometimes be quite simple and sometimes very challenging. Data from various countries show that this situation varies from region to region. In particular, the setup time and procedures involved in starting a business are important factors that can hinder the business setup process and demotivate entrepreneurs from making a new investment. This study therefore examines the extent to which entrepreneurs are affected by these factors. In the study, 10-year data of 87 different countries were used. These data consist of 3 different variables and include 2610 data in total. The findings demonstrated a positive and significant relationship between business setup time and procedures, a negative and significant relationship between procedures and starting a new business, a negative and significant relationship between business set up time and starting a new business. It was also revealed that procedures have a mediator role on the relationship between business setup time and starting a new business. The results of the study indicate that there should be a global reduction in the time-consuming aspects of business start-up procedures. Addressing these impediments to entrepreneurship and implementing policies that encourage the creation new investment in the economy are important tasks of governments. The research provides quantitative insights to researchers who aim to conduct future studies on this subject.